Peran Guru Dalam Meningkatkan Kemandirian Anak - Meilyana, Hayyu; Nurwita, Syisva; Imran, Ranny Fitria (Insititut Agama Islam Negeri (IAIN) Curup, 2023)
This study also aims to determine the constraints of teachers in increasing independence in children. This research is a qualitative descriptive research. Data d i ku m pu l k a n mel a lui ob s erv a s i, w a w a ncar a, d a n do k umn ta s i. The main subjects in this study are teachers and students at Jasa Mekar Mandiri Kindergarten, Seluma Regency. The results showed that 1) The role of teachers in improving children's independence in Jasa Mekar Mandiri Kindergarten Seluma Regency is: First the role as an educator is carried out by providing opportunities to children, and apply existing learning in schools. Second, the role as a teacher is carried out by the way the teacher chooses the right learning method, The teacher gives praise and motivation to the child. Third, the role as a guide is carried out in a way, teachers who habituate and repeat to children, teachers who have extensive knowledge, and teachers who instill neatness in children. Fourth, the role as a teacher assessor menggun akan daily records and report card . Teacher obstacles in increasing independence in early childhood in schools include: The surrounding environment, and Parenting. It can be concluded that the role of teachers in increasing children's independence is the role of teachers as educators, teachers, guides, and assessors.